PERSEPSI PENGELOLAAN HASIL HUTAN BUKAN KAYU (HHBK) OLEH MASYARAKAT DESA HANURA, KABUPATEN PESAWARAN, LAMPUNG - Gunardi Djoko Winarno; Irwan Effendi; Farida Fathul; Lestari Wibowo (University of Lampung, 2022)
Management of Non-Timber Forest Products (NTFPs) by the people of Hanura Village, Pesawaran Regency, Lampung in the Wan Abdul Rachman Forest Park is still limited to plants such as durian, Tangkil, areca nut, sugar palm, candlenut and other top canopy plants that cannot be relied for support basic household needs. On the other hand, the potential for understorey tree stands in forest areas has not been widely utilized for seasonal or commercial undergrowth species, due to farmers allegedly have not known yet about species of food crops which economically viable under stands. Meanwhile, farmers only know food crops for instance rice, corn, soybeans, cassava, sweet potatoes which can not be planted in forest areas. The effort to alleviate poverty and improve the welfare is through the development of porang plants which can be planted under mixed forest stands. For this reason, it is necessary to introduce and train porang to equalize their perceptions. The research method using Focus Group Discussion (FGD) and distributing questionnaires to 15 farmers. The results showed that the respondents in general were familiar with the porang plant, although not deeply. However, not many people know about porang development, so they are motivated to learn more, starting from nurseries, planting to harvesting.